Pendidikan Islam pada Zaman Khulafa Al-Rasyidin 632-661 M: Pertumbuhan dan Perkembangannya - Nurasia; pengelola, pengelola (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2023)
Muslims receive their religious education in Islam, which is based on the Qur'an and the Sunnah. This article examines the dynamics of development and change in Islamic education in the years after the passing of the Prophet Muhammad, may Allah bless him and grant him peace, notably the growth of Islamic education during the Khulaf-ur-Rsyidn era. described the different circumstances that led to the education system that was put in place at the time, as well as how it was applied to each caliph. The findings of this study suggest that, in general, the educational pattern during the reign of Caliph Abu Bakar radhyallahu 'anhu was unchanged from that of the Prophet Muhammad shallallahu 'alaihi wa sallam. Islam has developed quite quickly.